STEM-INTEGRATED PROJECT-BASED LEARNING (PJBL) MODEL AND LECTURE WITH EXPERIMENTS LEARNING MODEL: WHAT IS THE SCIENTIFIC LITERACY SKILLS OF ELEMENTARY TEACHER EDUCATION STUDENTS IN THESE LEARNING MODELS? - Duhita Savira Wardani; Medita Ayu Wulandari; Faridillah Fahmi Nurfurqon; Dian Kurniawati (Al-Bidayah : jurnal pendidikan dasar Islam, 2021)
This study aimed to determine the difference in students' scientific literacy skills between students who apply the PjBL model integrated STEM-assisted science literacy modules and students who apply lecture learning accompanied by experiments. The subjects of this study were 60 Elementary Teacher Education students who were divided into two classes at IKIP Siliwangi Bandung. This study used a comparative research method with a quantitative approach. The data collection method used was the scientific literacy skills test method. The test instrument in this study measured three scientific literacy competencies, namely the ability to explain scientific phenomena, evaluate and design scientific investigations, and interpret scientific data and evidence. The data were analyzed using descriptive analysis techniques and an Independent Sample T-Test. This study's results showed that the average scientific literacy ability of students who received the STEM-integrated PjBL model in this study was 83. The T-test of average students' scientific literacy ability showed that the PjBL model integrated STEM-assisted modules affected students' scientific literacy skills better than lecture learning accompanied by experiments. The recommendation of this study is further research to modify the STEM-integrated PjBL model assisted by this module to be more effective in improving students' ability to interpret scientific data and evidence.